2009
DOI: 10.1177/1049909108327588
|View full text |Cite
|
Sign up to set email alerts
|

Dyspnea—A Bad Prognosis Symptom at the End of Life

Abstract: The connection between dyspnea and sedation was clearly shown. There were significant differences between prevalent dyspnea and incident dyspnea groups.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(14 citation statements)
references
References 28 publications
0
13
0
1
Order By: Relevance
“…15,46,47 Multiple studies have also confirmed the prognostic role of dyspnea; in particular, patients with dyspnea at rest have a shorter rate of survival than those with episodic dyspnea alone. 48,49 …”
Section: Actuarial Estimation Of Survivalmentioning
confidence: 99%
“…15,46,47 Multiple studies have also confirmed the prognostic role of dyspnea; in particular, patients with dyspnea at rest have a shorter rate of survival than those with episodic dyspnea alone. 48,49 …”
Section: Actuarial Estimation Of Survivalmentioning
confidence: 99%
“…The PaP Score based on clinical and biochemical variables was statistically significant in a multivariate analysis, and validated in the training set and in an independent case series. 92 74 180 PPS, sex Yun et al, 2001 75 91 Terminal Cancer Prognostic Score (severe anorexia, diarrhoea, mild confusion) Schonwetter et al, 1990 76 172 Dressing ability, pulse rate, level of appetite, transferring ability Viganó et al, 2000 77 227 Primary lung cancer, presence of liver metastases, amount of weight loss (>8.1 kg within 6 months), LDH >681 U/l, serum albumin <35 g/l, lymphocyte count <1 x 10 9 /l, nausea and vomiting intensity, moderate-to-severe comorbidity (vs absent-to-mild), CPS <2 months (vs 2-6 and >6 months) Hardy et al, 1994 78 107 CPS, lung primary, intervention, dyspnoea, and decubitus ulcers Shadbolt et al, 2002 79 181 Self-rated health, appetite loss, emotional functioning, fatigue, diagnosis type, treatment Vigano et al, 2004 80 1006 Physical health-related quality-of-life factors (nausea, emesis, dyspnoea weakness) Park et al, 2006 81 142 European Quality of Life-5 Dimensions Tamburini et al, 1996 82 115 Confusion, cognitive status, global health status Lloyd-Williams et al, 2009 83 90 Depression, breathlessness, tiredness Caruso et al, 2010 84 83 Thrombocytopenia, Simplified Acute Physiology Score Cuervo Pinna et al, 2009 85 195 Prevalent dyspnoea Vitetta et al, 2001 86 102 Pain, dyspnoea, immobility, and adjusted Charlson comorbidity scores Cheung et al, 2009 87 198 Lack of appetite, drowsiness, dyspnoea, and fatigue Ventafridda et al, 1990 88 120 Appearance of unendurable symptoms and aggravation of previous controllable symptoms (dyspnoea, pain, delirium, vomiting) Zeng et al, 2011 89 808 Deterioration of global Edmonton Symptom Assessment System symptoms (pain, tiredness, nausea, depression, anxiety, drowsiness, appetite, well-being, dyspnoea) Tsamandouraki et al, 1992 90 202 Home care less effective compared with hospital care Caraceni et al 52 evaluated the impact of delirium on the survival of advanced cancer patients who were also assessed by using the PaP score. Delirium was found to significantly worsen the life expectancy associated with the PaP Score.…”
Section: Assessment Of Clinical Predictors Of Survivalmentioning
confidence: 99%
“…The presence of dyspnoea was noted in a few studies as an indication of patient survival. [85][86][87] Cuervo Pinna et al 85 found that patients with incident dyspnoea had higher average survival duration than those with prevalent dyspnoea. Vitetta et al 86 also described dyspnoea as having a negative effect on survival, along with pain, immobility, and adjusted Charlson comorbidity score.…”
Section: Assessment Of Clinical Predictors Of Survivalmentioning
confidence: 99%
“…Dyspnoea can have a profound effect on the physical, emotional and social well-being of patients and carers, leading to poor quality of life 8 9. It is an important predictor for poor survival10 in cancer patients and, as a refractory symptom, it increases the probability of sedation at the end-of-life 11…”
Section: Introductionmentioning
confidence: 99%